A Combined Experimental and Computational Approach to Study Crevice Corrosion of Stainless Steels. Issue 10 (8th October 2021) - Malki, B.; Berthomé, G.; Souier, T.; Boissy, C.; Guillotte, I.; Baroux, B.
Abstract : In the present work, a dual experimental and computational technique is used to study crevice corrosion of ferritic stainless steels in chloride-containing media. A specifically designed three-electrode set-up is developed to monitor current and potential during the incubation, initiation and propagation stages. At the same time, a 3D finite element model is implemented to examine the galvanic coupling prevailing in the experimental set-up and to provide a mechanistic interpretation of the obtained results. The asymptotic current and potential measured at the end of the experiments are thought to be more realistic indicators of crevice corrosion kinetics than the commonly used depassivation pH. The technique also allows highlighting several physicochemical effects including chloride concentration, pH, temperature as well as the effect of surface pretreatment. Finally, an in-depth examination of the simulated current and potential distributions inside the crevice reveals that any extension of the propagation outside the confined geometry will report the ohmic drop out of the crevice, which radically impacts the initiation and propagation modes.